Implikasi Yuridis Presidential Threshold Dalam Pemilu Presiden Terhadap Prinsip Kedaulatan Rakyat - Muhsin (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
This study aims to analyze the juridical implications of implementing the presidential threshold in Indonesia's presidential elections on the principle of popular sovereignty as guaranteed by the 1945 Constitution of the Republic of Indonesia. Using a normative juridical approach and literature review method, this research examines Article 222 of Law Number 7 of 2017 along with relevant Constitutional Court decisions and academic perspectives. The findings indicate that the presidential threshold restricts citizens' political rights and undermines fair representation in the electoral process. This policy tends to strengthen political oligarchy, limiting smaller parties from nominating presidential candidates and narrowing the public’s choices in elections. Although the Constitutional Court has upheld the threshold as a matter of open legal policy, many scholars argue that its implementation contradicts the spirit of inclusive democracy and the core principle of popular sovereignty. Therefore, the existence of the presidential threshold should be reconsidered to ensure that Indonesia’s electoral system reflects democratic values that are fair, participatory, and uphold the equal political rights of every citizen. Reformulating this policy is essential to strengthen electoral legitimacy and broaden constitutional political participation.